Kesenjangan Antara Harapan Dan Kenyataan Mengenai Sikap Positif Terhadap Kedaulatan Rakyat Dalam SistemPemerintahan Indonesia Analisis Isi Buku Teks Pendidikan Pancasila dan Kewarganegaraan Terbitan Kementerian Pendidikan dan Kebudayaan Republik Indonesia Kelas VIII SMP/MTs Kurikulum 2013 dan Berita di Media Internet dan Online - Desiany, Ega Marshalita; , Dra. Hj. Sri Arfiah, S.H, M.Pd (2015)
This study is aim to discribe the stages of a positive attitude towards the sovereignty of the Indonesia goverments system in the Pendidikan Pancasila and Kewarganegaraan book published by the ministry of education and culture republik of Indonesia class VIII SMP/MTs 2013 curriculum. To disrcribe the positive attitude toward the sovereignty in the governance system of indonesia based on the material in the internet and media online, to describe the gap between the expectation and the positive attitude reality toward sovereignty in the goverence system of Indonesia. The type of this research is qualitative research the sources of the data in this researchis Pendidikan Pancasila and Kewarganegaraan book published by the ministry of education and culture republic of Indonesia class SMP/MTs 2013 curriculum, and news material on the internet media and online. The techniques for collecting use the documentation and literature study, the validity of the data to analyze the data that has been collcted used interactive analysis. Result of the research can be concluded that happened discrepancy a positive attitude of the sovereignty in the goverment system of Indonesia, between the expectations contained in the text book Pendidikan Pancasila and Kewarganegaraan issue the ministry of education and culture of the republic of Indonesia SMP/MTs VIII class curriculum to 2013 with the fact obtained on the internet media and online. The discrepancy can be seen of the incident that deviate from the existing theory. There are goverments that made the society disapponted with them and behave is incompatible with the theory in the book.